Non-autotrophic methanogens dominate in anaerobic digesters - Atsushi Kouzuma (Nature Portfolio, 2017)
Abstract Anaerobic digesters are man-made habitats for fermentative and methanogenic microbes, and are characterized by extremely high concentrations of organics. However, little is known about how microbes adapt to such habitats. In the present study, we report phylogenetic, metagenomic, and metatranscriptomic analyses of microbiomes in thermophilic packed-bed digesters fed acetate as the major substrate, and we have shown that acetoclastic and hydrogenotrophic methanogens that utilize acetate as a carbon source dominate there. Deep sequencing and precise binning of the metagenomes reconstructed complete genomes for two dominant methanogens affiliated with the genera Methanosarcina and Methanothermobacter, along with 37 draft genomes. The reconstructed Methanosarcina genome was almost identical to that of a thermophilic acetoclastic methanogen Methanosarcina thermophila TM-1, indicating its cosmopolitan distribution in thermophilic digesters. The reconstructed Methanothermobacter (designated as Met2) was closely related to Methanothermobacter tenebrarum, a non-autotrophic hydrogenotrophic methanogen that grows in the presence of acetate. Met2 lacks the Cdh complex required for CO2 fixation, suggesting that it requires organic molecules, such as acetate, as carbon sources. Although the metagenomic analysis also detected autotrophic methanogens, they were less than 1% in abundance of Met2. These results suggested that non-autotrophic methanogens preferentially grow in anaerobic digesters containing high concentrations of organics.